Deep seabed mining: Frontiers in engineering geology and environment - Guo, Xingsen; Fan, Ning; Liu, Yihan; Liu, Xiaolei; Wang, Zekun; Xie, Xiaotian; Jia, Yonggang (International journal of coal science & technology, 2023)
Ocean mining activities have been ongoing for nearly 70 years, making great contributions to industrialization. Given the increasing demand for energy, along with the restructuring of the energy supply catalyzed by efforts to achieve a low-carbon economy, deep seabed mining will play an important role in addressing energy- and resource-related problems in the future. However, deep seabed mining remains in the exploratory stage, with many challenges presented by the high-pressure, low-temperature, and complex geologic and hydrodynamic environments in deep-sea mining areas, which are inaccessible to human activities. Thus, considerable efforts are required to ensure sustainable, economic, reliable, and safe deep seabed mining. This study reviews the latest advances in marine engineering geology and the environment related to deep-sea mining activities, presents a bibliometric analysis of the development of ocean mineral resources since the 1950s, summarizes the development, theory, and issues related to techniques for the three stages of ocean mining (i.e., exploration, extraction, and closure), and discusses the engineering geology environment, geological disasters, in-situ monitoring techniques, environmental protection requirements, and environmental effects in detail. Finally, this paper gives some key conclusions and future perspectives to provide insights for subsequent studies and commercial mining operations.